Identification of extremely hard coke generation by low-temperature reaction on tungsten catalysts via Operando and in situ techniques - Thotsatham Takkawatakarn (Nature Portfolio, 2021)
Abstract The coke formation in the catalytic system mainly cause to the catalyst deactivate resulting the dramatic decreasing of the catalyst performance then the catalyst regeneration was required. In this study, adding MgO physically mixed with WO3/SiO2 catalysts were prepared and compared with the ones prepared by physically mixing with SiO2. Adding MgO affected the generation of new species of coke deposited on WO3/SiO2 and MgO itself. Comparing the reaction temperature when adding MgO between at 300 and 450 °C, the different pathway of reaction and the coke formation were found. At 450 °C, the metathesis reaction was more pronounced and the lower temperature of coke deposited on WOx/SiO2 was found. Surprisingly, the extremely hard coke occurred during reaction at 300 °C that the maxima of coke formation was found over 635 °C. This due to the fact that the reduction of reaction temperature from 450 to 300 °C affected the decreasing of the metathesis activity. Conversely, the increasing of dimerization and isomerization of butenes-isomer was observed especially 1-butene and iso-butene. Thus, it could suggest that those quantity of them play the important role to generate the charged monoenyl or cyclopentenyl species by participating with ethene through the dimerization, resulting in the formation of extremely hard coke.